#184 Anticonvulsant activities of the leaves of canavaliagladiata(Jacq.) DC. Using zebra fish - C, Velmani; T, Shri Vijaya Kirubha; R, Senthamarai (Journal of Pharmaceutical Chemistry, 2022)
Epilepsy is one of the most common serious neurological disorders, responsible for substantial morbidity and mortality due to the limited efficacy and negative properties of antiepileptic drugs. Epilepsy treatment is based on the use of drugs that aim to inhibit repetitive neuronal discharges, and consequently, the recurrence of seizures. However, despite the large number of antiepileptic drugs currently available, about 30-40% of patients with epilepsy do not respond satisfactorily to treatments. Therefore, the investigation of new therapeutic alternatives for epilepsy becomes relevant, especially the search for new compounds with anticonvulsant properties. The therapeutic potential of plant-derived bioactive compounds has been a target for alternative treatments for epilepsy. Medicinal plants used for the treatment of epilepsy are potentially a valuable source of novel antiepileptic small molecules. To identify anticonvulsant secondary metabolites, we performed an in-vivo, zebrafish-based screen of medicinal plants used in Southeast Asia for the treatment of seizures. Canavalia gladiata (Jacq.) Dc belonging to the family Papilionaceae was identified as having significant anticonvulsant activity in zebrafish with seizures induced by the pentylenetetrazol (PTZ). The use of animal models for drug screening, such as zebrafish, contributes to a better understanding of the mechanisms involved in seizures and for investigating methods and alternative treatments to decrease seizure incidence. The sensitivity of zebrafish to chemoconvulsants and its use in genetic approaches reinforces the contribution of this animal to epilepsy research. Moreover, we summarize advances in zebrafish-based studies that focus on plant-derived bioactive compounds with potential antiseizure properties, contributing to the screening of new drugs for epilepsy treatment.